2002
DOI: 10.2337/diacare.25.7.1117
|View full text |Cite
|
Sign up to set email alerts
|

A Longitudinal Study of the Effects of a Gluten-Free Diet on Glycemic Control and Weight Gain in Subjects With Type 1 Diabetes and Celiac Disease

Abstract: OBJECTIVE—To describe the longitudinal growth characteristics and glycemic control in type 1 diabetic children diagnosed with celiac disease and started on a gluten-free diet (GFD). RESEARCH DESIGN AND METHODS—Data on growth and glycemic control for 11 case subjects diagnosed with celiac disease (cd+ group) and started on a GFD were collected prospectively, and two control subjects without celiac disease matched for age, sex, and duration of diabetes (cd− group) were selected for comparison. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
80
6
4

Year Published

2003
2003
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(103 citation statements)
references
References 32 publications
9
80
6
4
Order By: Relevance
“…In accordance with this finding, some previous researchers have reported an impairment of growth in patients with celiac disease and type 1 diabetes compared with diabetic control subjects (3,9). In longitudinal studies of diabetic patients consuming a GFD, Amin et al (9) found an increase in BMI SDS, Saadah et al (10) showed an increase in weight-for-age z scores, and SanchezAlbisua et al (12) found an increase in height SDS in patients with good dietary compliance. On the other hand, Rami et al (11) and Westman et al (24) found no improvement in neither BMI SDS or height SDS on a GFD.…”
Section: Statisticssupporting
confidence: 68%
See 1 more Smart Citation
“…In accordance with this finding, some previous researchers have reported an impairment of growth in patients with celiac disease and type 1 diabetes compared with diabetic control subjects (3,9). In longitudinal studies of diabetic patients consuming a GFD, Amin et al (9) found an increase in BMI SDS, Saadah et al (10) showed an increase in weight-for-age z scores, and SanchezAlbisua et al (12) found an increase in height SDS in patients with good dietary compliance. On the other hand, Rami et al (11) and Westman et al (24) found no improvement in neither BMI SDS or height SDS on a GFD.…”
Section: Statisticssupporting
confidence: 68%
“…In the present study, A1C was almost unchanged in patients consuming a GFD. In a few studies, a decrease in A1C was seen in diabetic subjects after a GFD (9,12), whereas others could not demonstrate any improvements (10,11,25,26). However, A1C may not by itself reflect the metabolic control in diabetic subjects consuming a GFD.…”
Section: Statisticsmentioning
confidence: 99%
“…Subclinical celiac disease, like symptomatic illness, may also cause growth failure and decreased weight gain (9,10), at least in some patients. A cross-sectional Australian study showed small reductions in height and weight Z score in 20 diabetic children with subclinical celiac disease compared with 40 diabetic control subjects matched for age, sex, and duration of diabetes (11), while an English study (12) reported decreased BMI Z scores but normal height in 11 diabetic children with celiac disease (10 subclinical and 1 classic) at the time of diagnosis (age 2.6 -17.3 years). Nevertheless, studies by Cacciari et al (13) and Bode et al (14) found that patients with subclinical celiac disease reach normal adult height even if untreated during childhood or adolescence.…”
Section: The Case For Screening-michael Freemarkmentioning
confidence: 99%
“…Erratic absorption of nutrients in symptomatic celiac disease may increase the risk of severe hypoglycemia in diabetic patients; the effects on glycemic control and HbA 1c are more variable (7,8,12 and citations within).…”
Section: The Case For Screening-michael Freemarkmentioning
confidence: 99%
“…However, the improvement in factors related to coeliac disease, such as growth, villous architecture and biochemical indices, also applies to patients with type 1 diabetes, and a trend towards increased BMI and tighter glycaemic control has been reported [8]. Another effect of the glutenfree diet is relief from non-specific symptoms such as tiredness and abdominal discomfort as well as a reduced risk of long-term complications such as infertility, osteoporosis and lymphomas of the small intestine.…”
mentioning
confidence: 99%